2019
DOI: 10.1155/2019/5049752
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Factors Associated with Precervical Cancer among Screened Women in Southern Ethiopia

Abstract: Background. Cervical cancer is one of the major noncommunicable public health problems among the female population affecting not only the women but also the whole community. Annually, more than half a million new patients are diagnosed with it and over 270,000 deaths occur worldwide. There are very few research efforts conducted on prevalence and associated factors of specific target group in the region. So, this study tries to show the magnitude on all women screened for precervical cancer and serves as a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 11 publications
(13 reference statements)
7
28
4
1
Order By: Relevance
“…The minimum prevalence of precancerous lesions of the cervix was 6.7% as reported in a study conducted in Tigray region [ 14 ]. The highest, 27.7% was observed in a study conducted in SNNPE [ 20 ]. The I 2 test result showed high heterogeneity (I2, 93.2%, p = <0.001).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The minimum prevalence of precancerous lesions of the cervix was 6.7% as reported in a study conducted in Tigray region [ 14 ]. The highest, 27.7% was observed in a study conducted in SNNPE [ 20 ]. The I 2 test result showed high heterogeneity (I2, 93.2%, p = <0.001).…”
Section: Resultsmentioning
confidence: 98%
“…All the included studies were published between 2013 and 2019. We included both cross-sectional and case-control studies using an estimated sample size range from 284 [ 17 ] up to 528 [ 20 ]. About 5,108 women aged from 18–85 years were included to estimate the pooled prevalence of precancerous lesions of the cervix and its associated factors among women in Ethiopia Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В 2016 г. D. López-Hernández et al отметили прямую связь с числом половых партнеров (ОШ = 1,1; 95% ДИ: 1,02-1,15) [6]. Также исследователи отмечают такие факторы риска, как курение (ОШ = 3,7; 95% ДИ: 1,4-9,9), наличие двух и более половых партнеров на протяжении жизни (ОШ = 2,2; 95% ДИ: 1,1-4,7), возраст первого полового акта менее 18 лет (ОШ = 6,6; 95% ДИ: 3,14-13,0) [13], что в целом совпадает с полученными нами результатами.…”
Section: результаты исследования и их обсуждениеunclassified
“…In Ethiopia, different studies done among women indicated that factors associated with knowledge towards cervical cancer screening evidenced such as educational status, occupational status, marital status, monthly household income, used modern contraceptive, multiple sexual partners, and sexually transmitted disease. Besides, women didn't know the screening method and largely indicated a lack of knowledge towards the persistence of cervical cancer screening and negative perception towards cervical cancer screening [11,12,14,15]. However, little is known about knowledge towards cervical cancer screening of urban health extension workers in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%